2020
DOI: 10.2478/bhk-2020-0008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intermittent negative pressure and active recovery therapies in the post-match period in elite soccer players: A randomized, parallel arm, comparative study

Abstract: SummaryStudy aim: This study compared the effects of intermittent negative pressure therapy (INPT) vs. active recovery therapy (ART) on post-match physiological parameters such as serum CK level and skin temperature of the lower limbs in elite soccer players.Material and methods: Twenty healthy male professional soccer players from a Brazilian first division soccer club were enrolled in this randomized, parallel arm, open label, comparative study. After participating in 2 soccer matches, they were randomly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Similar results indicating a lack of IPC effect were found in previous research [ 27 , 28 , 32 ]. A significant difference in strength was observed by Fonda et al (2015), while van Rensburg et al (2017) and Maior et al (2020) did not compare strength in their studies [ 12 14 ]. Further research is required to determine whether and in what patient groups INP or IPC might be effective in muscle strength recovery in DOMS.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Similar results indicating a lack of IPC effect were found in previous research [ 27 , 28 , 32 ]. A significant difference in strength was observed by Fonda et al (2015), while van Rensburg et al (2017) and Maior et al (2020) did not compare strength in their studies [ 12 14 ]. Further research is required to determine whether and in what patient groups INP or IPC might be effective in muscle strength recovery in DOMS.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study demonstrated a more significant CK decrease after INP than after active recovery therapy. However, the participants were not blinded, and therefore a placebo effect cannot be ruled out [ 14 ]. The study was also carried out on professional soccer players after playing a full match, making it difficult to compare results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, over time, many changes have occurred. Many studies state that active recovery is better used after exercise than passive recovery (Akagi et al, 2020;Lopes et al, 2014;Maior et al, 2020;Mika et al, 2016). However, one previous study stated that there was no difference in the effect between passive and active recovery after exercising.…”
Section: Discussionmentioning
confidence: 99%